EKSISTENSI PEDAGANG ETNIS MINANGKABAU DI PERANTAUAN (Studi pada Pedagang Sate Padang di Jalan Delima Kota Pekanbaru) - Nofia Noor Husanah; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Existence of Minangkabau Ethnic traders in Overseas (a study of trader Padang sate on Street Delima Pekanbaru City). This research was conducted in Pekanbaru City. The purpose of this research is to find out how the development efforts made by Minangkabau ethnic satay traders in Pekanbaru and to find out the obstacles and driving factors that are done by these satay traders to maintain their existence. In determining the research subject using purposive sampling technique that is predetermined based on criteria. The number of informants in this study amounted to 4 people. The theory used is the theory of strategy from Pierre Bourdieu. The results of this research are that informants make efforts to develop their business using several strategies such as making savings by setting aside some of their money by saving, investing, being able to accept and learn all the trade knowledge from the closest people and bequeath their merchandise to offspring, maintain economic capital and capital social in order to earn an income and perpetuate its business, but it also seeks to preserve and improve social recognition by having a distinctive feature. In carrying out this strategy, there are motivating factors for informants to carry out this strategy which is useful for sustaining business. In addition, of course there are inhibiting factors obtained by the informant namely in maintaining the characteristics, attracting customers, etc. There are also some satay traders who have no obstacles such as the absence of obstacles in attracting customers because their businesses already have names. Basically, every trader has different problems in running their business. Keywords: Strategy, Traders Sate Padang